Perempuan Pengrajin Gerabah di Desa Wanio Kecamatan Pancalautang Kabupaten Sidenreng Rappang - Syamsiah, Syamsiah; Suhaeb, Firdaus W. (Program Studi Sosiologi, 2020)
This study aims to describe the condition of women who work as pottery craftsmen. This type of research is descriptive qualitative. Data collection methods in this study are through interviews, observation, and documentation. The target of this research is women craftsmen of pottery in the village of Wanio, kec. Pancalautang Kab. Sidrap then selected 7 people who became research informants through a purposive sampling technique, with the criteria being women pottery craftsmen who are married, as pottery craftsmen and whether or not they have been working as pottery craftsmen for a long time. The results showed the profile of the life of the first pottery craftsman from the education aspect, the second the health aspect and the third the income aspect. The woman who craftsmen divides her time in carrying out the two domains at once, namely directly making pottery and there are also those who finish work at home before making pottery. The positive impact felt by women in making pottery is that it can help the family economy besides that it can increase a sense of self-esteem, life satisfaction and health is maintained. The negative impacts are lack of time with family and workload.